APAKAH MODEL PEMBELAJARAN DENGAN MIND MAPPING DAPAT MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR ? - I Ketut Suardika; Abindarda Abindarda; Sakka Hasan (Universitas Muhammadiyah Makassar, 2020)
Mind mapping is essential in shaping students' ability to think. In mind mapping, students are allowing sharing the thoughts they have learned into diagrams or patterns. The purpose of this study is to provide information about the feasibility of learning with a mind mapping model. In addition, this study will explain how the mind mapping learning model can improve student learning outcomes, especially elementary school students. This study uses a Classroom Action Research (CAR) design which divides the implementation phase into two cycles. The research location is located in the 96 Elementary School in Kendari City with the research subject of class Vb. Topic subjects used were